Taking offense: Religion, art and visual culture in plural configurations, by Christiane Kruse, Birgit Meyer, and Anne-Marie Korte (eds.) 2018 - Tammy Wilks (Journal for the Study of Religion)
What makes an image or performance offensive? Scholars of religion have direct interests in this question. The question is central to the expanding study of material religion - the theory that things, like images, have agency because they are 'caught up', as Ingold (2007:1) states, in the currents of our life worlds and epistemologies (cf. Meyer, Morgan, Paine & Plate 2010:7). To ask then, 'What makes an image offen -sive?' (Meyer et al. 2018:11) is to understand that, what counts as offense, is determined by a particular set of conditions and configurations of power by 'interpretative communities' (Chidester 2018:291) who use the potency of images to negotiate being human. The authors of Taking offense engage the above question as a hermeneutic that brings chapters in a 'multidisciplinary conversation' (Meyer et al. 2018:10). This approach frames the book not only as a collection of the authors' interpretation of this question, but as a reflection of the conceptual irretrievability of offense.